Analysis of Shift in Translation on The Usage Instruction of Skincare Products - Ni Wayan Nandira Paraswari; Ni Luh Sutjiati Beratha; I Komang Sumaryana Putra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines the translation of instructions for using skin care products from English into Indonesian, focusing on translation shifts as defined by Catford (1965). These shifts include level shifts and category shifts (structure, class, unit and intra-system shifts). This research analyzes how these shifts occur and adapt to the Indonesian linguistic and cultural context. Data from brands including Wardah, Avoskin, and Garnier were collected and analyzed using a qualitative descriptive method. The findings highlight common shifts, like structural changes due to syntactic differences and word class shifts to maintain meaning. Understanding these shifts can improve translation strategies, ensuring that bilingual packaging is clear, accurate, and culturally appropriate, thus increasing consumer understanding and satisfaction.